Building Pocket Code build-variants - Kumar Luhana, Kirshan; ., . (International Journal of Engineering and Technology, 2018)
Pocket Code is an integrated development environment (IDE) targeted at smartphones. With this IDE users can create mobile apps for the block-based visual programming language Catrobat. Pocket Code is released in various flavors with custom features for partners and projects (e.g., Pocket Code, Create@School, Phiro, and Standalone). All flavors extend a single common project codebase according to flavor specific requirements. The Standalone variants (debug and release) convert a Catrobat project into an Android application to install it independently and execute it without the need for an installed Pocket Code on an Android smartphone. Furthermore, it can be published on app stores for reputational and also monetary benefits. The app resource files and the configuration are generated on the fly upon a user request via the Pocket Code sharing platform. In this paper, the approach of building a Pocket Code variant and transform a Pocket Code project into an Android application are described. Especially the Standalone build variants have the potential to bring many interesting apps to the market.Â Â